PRODUCT QUALITY, INFLUENCE OF PRICE AND E-COMMERCE ON PEOPLE'S BUYING INTEREST ON UMKM - Arif, Muhammad (International Proceeding of Law and Economic, 2021)
Buying interest is a condition where a person is interested in a product and has the intention to buy the product, but at this stage the actual buying process has not occurred. At restaurant X in Kota Tebing Tinggi, it was found that the price of the product was slightly more expensive than competitors, the quality of the food was sometimes non-standard, and the unavailability of e-commerce.This is a factor that can affect customer buying interest. This study aims to determine the effect of price, product quality, and e-commerce on the buying interest of the customers of Restaurant X in Tebing Tinggi City. The type of research used in this research is quantitative research usingexplanatory research approach.The population in this study were all customers of restaurant X. The sample in this study amounted to 100 respondents. The data analysis technique used multiple linear regression analysis. The results of hypothesis testing are known that there is a significant effect between price on buying interest (sig = 0.000 and t = 3.613). There is a significant effect of product quality on buying interest (sig.=0.000 and tcount=5.253). There is no significant effect between e-commerce on buying interest (sig.=7,780 and tcount=0,280). There is a significant effect between price, product quality, and e-commerce on buying interest (sig. = 0.000 and Fcount = 19.221). The value of R Square (0.375) which means price, product quality, and e-commerce contribute to buying interest by 37.5%. The conclusion of this study is that there is a significant effect of price on the buying interest of the customers of Restaurant X in Tebing Tinggi City. There is a significant effect of product quality on the buying interest of the customers of Restaurant X in Tebing Tinggi City. There is no significant effect of e-commerce on the buying interest of Restaurant X customers in Tebing Tinggi City. There is a significant influence between price, product quality, and e-commerce on the buying interest of the customers of Restaurant X in Tebing Tinggi City